Revisiting Nanotoxicology Tests—Miniaturized Approaches of Nanotoxicity Tests in Daphnids - Anne Leung; Emma Rowan; Dimitrios Kakavas; Konstantinos Panagiotidis; Keith D. Rochfort; Konstantinos Grintzalis (Proceedings)
The great increase in nanotechnology in the last 20 years has led to the alarming presence of nanomaterials in the environment as a new category of pollutants. Given the fact that legislation on nanomaterials is not concrete, the monitoring of their toxicity responses remains central. Focusing on tests in aquatic environments, daphnids are commonly employed as a bioindicator species for experiments with nanomaterials. However, until now, there has not been a unified and agreed approach to nanotoxicity testing, while research among different laboratories has been performed with significantly different setups, which may affect the reproducibility of the results. In this study, daphnids were exposed to silver nanoinks and the impact of surface to volume was assessed by comparing shallow vessels such as Petri dishes with deeper exposure vessels. Furthermore, in an attempt to assess whether the tests can be performed in smaller volumes, and thus in miniaturized versions, experiments compared larger and smaller volume setups. Finally, another parameter explored was the crowding of animals in exposure, and therefore their absolute number. Mortality was affected by both surface to volume and miniaturization, and significantly with crowding, supporting the implication of the number of animals in the tests. Further investigation with molecular and phenotypic endpoints confirmed these changes.